Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis

Queer Theory and Sociology: Locating the Subject and the Self in Sexuality Studies - Isaiah Green, Adam (Sociological Theory, 2007)
In this paper, I revisit the relationship of queer theory and sociology in order to address some critical issues around conceiving the subject and the self in sexualities research. I suggest that while sociology and queer theory are not reducible to each other, sociology has its own deconstructionist impulse built into pragmatist and symbolic interactionist analyses of identity and subjectivity that is often overlooked by or reinvented through queer theory. But, conversely, queer theory has a very specific deconstructionist raison d'etre with regard to conceiving the sexual subject that marks its key departure from Foucault and sociology more generally. This deconstructionist mandate, by definition, moves queer theory away from the analysis of self and subject position—including those accruing from race, class and gender—and toward a conception of the self radically disarticulated from the social. This “anti-identitarian” position has been a source of criticism among some sociologists who find in queer theory an indefensible “refusal to name a subject” ( Seidman 1993:132). But this criticism, I suggest, stems from a misplaced effort to synthesize queer theory and sociology when, in fact, the two approaches to the subject are founded on incommensurable methodological and epistemological principles. Rather, I argue that the very promise of queer theory rests in a strong deconstructionism that exists in tension with, rather than as an extension of, sociological approaches to the self
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; thématiques

Pink blood: la violence homophobe au Canada : essai - Janoff, Douglas (Triptyque, 2007)
Essai traduit de l'anglais sous la direction de Diane Archambault Livre unique en son genre, Pink Blood est la première étude de cas de portée nationale à paraître en français sur le thème de la violence homophobe. Fruit de neuf ans de recherche, il couvre plus de 350 agressions et quelque 120 homicides perpétrés au Canada sur la personne de gais et de lesbiennes entre 1990 et 2004. L’ouvrage analyse avec minutie l’impact de la violence homophobe dans une démocratie qui s’enorgueillit d’accorder « l’égalité » à tous ses citoyens… Certains Canadiens seraient-ils plus égaux que d’autres? De Whitehorse à St. John’s en passant par Montréal et Québec, l’auteur pose les questions suivantes: Comment la police fait-elle enquête sur ces crimes et comment les enregistre-t-elle? Quel traitement leur réserve le système judiciaire? Comment les médias présentent-ils ces incidents? Quels programmes et politiques ont soulevé la question de la violence homophobe et transphobe et quels sont ceux qui sont passés à côté de la question? La version anglaise de l’ouvrage, parue en 2005 aux Presses de l’Université de Toronto, a été retenue dans le programme d’enseignement de plusieurs facultés universitaires canadiennes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; histoire et politique; homophobie; hétérosexisme; premier cycle; périodes historiques; régions géographiques; soc2014; systèmes d'oppressions; thématiques; violences

Homosexualités: variations régionales - Julien, Danielle; Lévy, Joseph J. (Collection Santé et société, 2007)
Les études sur l'homosexualité ont, à ce jour, essentiellement porté sur les milieux urbains, négligeant les autres milieux de vie comme les petites villes et les régions rurales, où les conditions socioculturelles peuvent contribuer à amplifier les difficultés de dévoilement et d'expression publique de l'identité ou des préférences sexuelles. La rareté ou l'absence de réseaux associatifs ou de rencontres et la carence de ressources d'aide dans le domaine de la santé et des services sociaux pourraient aussi contribuer à l'isolement ainsi qu'aux sentiments d'aliénation et de malaise chez ces personnes. Afin de mieux cerner ces enjeux, les auteurs analysent les réalités quotidiennes, sociales, relationnelles et sexuelles de lesbiennes et gais vivant en région. Ils explorent les dimensions touchant la famille et l'homoparentalité, ainsi que les variations dans les usages grâce à Internet et à l'intervention en ligne. Ces réflexions pourront sans doute aider à mieux comprendre les réalités des personnes homosexuelles vivant à l'extérieur des grands centres et, ainsi, orienter des interventions psychosociales plus adaptées chez ces populations encore négligées.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; hétérosexisme; identités LGBTQIA2+; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Fear of a queer planet queer politics and social theory - Warner, Michael; Social Text Collective (University of Minnesota Press, 2007)
In recent years, lesbians and gay men have developed a new, aggressive style of politics. At the same time, innovative intellectual energies have made queer theory an explosive field of study. In "Fear of a Queer Planet", Michael Warner draws on emerging new queer politics, and shows how queer activists have come to challenge basic assumptions about the social and political world. Existing traditions of theory - Marxism, cultural studies, psychoanalysis, anthropology, legal theory, nationalism, and antinationalism - have too often presupposed a heterosexual society, as the essays in this volume demonstrate. "Fear of a Queer Planet" suggests a new agenda for social theory. It moves beyond the idea that lesbians and gay men share a minority identity and special interests and that their issues can be subordinated to more general social conflicts. Instead, Warner and the other contributors to this volume show that queer sexualities take many forms, are the subject of many kinds of conflict and struggles, and must be taken as a starting point in thinking about cultural politics. This collection explores the impact of ACT UP, Queer Nation, multiculturalism, the new religious right, outing, queerness, postmodernism, and other shifts in the politics of sexuality. The authors featured speak from different backgrounds of gender, race, nationality, and discipline. Together, they show how struggles over sexuality have profound implications for progressive politics, social theory, and cultural studies. Michael Warner has written extensively on censorship and the public sphere, the construction of American literary history, and the social and political implication of literary theories. He is author of "The Letter of the Republic: Publication and the Public Sphere in Eighteenth-Century America" and co-editor of "The Origins of Literary Studies in America: A Documentary Anthology".
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; histoire et politique; militance; premier cycle; périodes historiques; queer; science politique et droit; sciences politiques; soc2014; thématiques; théories sociales